Diagnostic performance of protein induced by vitamin K absence II for chronic hepatitis B-related hepatocellular carcinoma - Wan, Jianxin; Su, Jiachun; Ye, Zhuangjian; Huang, Chumei; Liang, Jianbo; Liu, Min; Luo, Jinmei; Li, Laisheng (Journal of Laboratory and Precision Medicine, 2019)
Background: The aim of this study was to assess the diagnostic value of prothrombin induced by vitamin K absence-II (PIVKA-II) for hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) in a Chinese population. Methods: In this study, receiver operating characteristics (ROC) curve was plotted, and the area under the ROC curve (AUC) was calculated to assess the diagnostic performance of serum PIVKA-II levels for HBV-related HCC (n=134) with negative or mildly elevated α-fetoprotein (AFP) relative to chronic hepatitis B (CHB, n=119) patients or healthy controls (n=100). Results: Serum levels of PIVKA-II were significantly greater in the HBV-related HCC patients compared to the CHB patients (P